Frequency of Skip Metastasis to the Cervical Lymph Nodes in Oral Squamous Cell Carcinoma (IAHS Medical Journal, 2022)
Background: Oral Squamous Cell Carcinoma (OSCC) commonly spreads across regional lymph nodes. Presence or lack of metastasis to the cervical lymph nodes is an essential prognostic factor. The regional metastatic pattern to the cervical lymph nodes is defined as the orderly involvement of the successive anatomical lymph node levels. When the sequential order of involvement is lost and metastases are found at a lower level without involving the first echelon nodes or groups of intermediate nodes, then it is called skip metastases. Knowledge of Skip metastases will allow patients to prevent from receiving under and overt therapy. Current treatment of oral squamous cell carcinoma is primary resection followed by elective/therapeutic neck dissection. Regarding neck dissection, there is a dilemma that up to which level should be performed. Some prefer up to level III and some prefer up to level IV based on evidence of skip metastasis to level IV. This study conducted to find out the frequency of skip metastasis and its pattern according to the site, size and grading of primary oral squamous cell carcinoma.Materials and methods: This was a cross sectional study performed in between August 2018 to September 2019 among 58 patients having histologically proven oral squamous cell carcinoma of tongue, buccal mucosa and retro molar trigone undergoing elective and therapeutic neck dissection. Cervical lymph nodes along with fibro-fatty tissue from patients underwent neck dissection except super selective neck dissection were fixed with 10% formalin in separate containers. The containers were marked with nodal level and sent to pathology department for histopathological examination.Results: Out of 58 patients, 32 (55.2%) had cervical nodal metastasis on postoperative histopathology report, 26 (44.8%) patients had no nodal metastasis and 7 (12.1%) developed skip metastasis. Oral squamous cell carcinoma of tongue was found to be the most frequent site to develop skip metastasis to the cervical lymph node. Also, skip metastases were relatively higher in greater tumour grading and T-stages.Conclusion: Chances of skip metastasis should be considered during treatment planning, especially for oral squamous cell carcinoma of the tongue. For the majority of cases with N0 neck, elective neck dissection up to level III should be performed. In case of carcinoma of Tongue, high-grade tumour and advanced T-stages, elective neck dissection should be performed up to level IV.IAHS Medical Journal Vol 4(2), December 2021; 36-40